Tramadol suppository poisoning in children of Bangladesh (Bangladesh Journal of Child Health, 2020)
Background: Tramadol is an analgesic agent utilized in the treatment of different types of pain. Recently it was found that a few cases of tramadol poisoning were observed in hospitalized children. In all cases, it happened due to accidental administration of tramadol suppository.Objective: The aim of this study was to determine the clinical manifestations of tramadol suppository poisoning in children and to create public awareness about the prevention of this suppository poisoning.Materials & Methods: This was an observational, retrospective, single-center caseseries study of hospitalized children in Dhaka Shishu Hospital during the periods of July 2016 to March 2017. Eleven patients with history of accidental intake of tramadol suppositories were enrolled in this study. Data regarding risk factors and clinical features were recorded and analyzed.Results: In this study, 7/11(64%) cases were male and 4/11(36%) female. Mean age was 7.8 month and mean duration of hospital stay was 46.4 hours. Parecetamol in 2/11 (18%) cases and glycerin suppository in 9/11(82%) cases were main drugs that were supposed to be introduced instead of tramadol. Keeping drugs in same containers (11/11), similarities of suppository’s size, shape and color (11/11) were found as causes of mistakes in this study. Main clinical features were drowsiness in 4/11(36%) cases, tachycardia in 3/11(27%) cases and one case died.Conclusions: More cautiousness of parents, dissimilarity among different suppository in color size, shape and using of different containers of drugs may be the preventive way of this poisoning.Bangladesh J Child Health 2019; VOL 43 (3) :157-160